Effects of aronia berry (poly)phenols on vascular function and gut microbiota: a double-blind randomized controlled trial in adult men - Istas, Geoffrey; Wood, Eleanor; Le Sayec, Melanie; Rawlings, Claudia; Yoon, Jeeyoung; Dandavate, Vaishnavi; Cera, Debora; Rampelli, Simone; Costabile, Adele; Fromentin, Emilie; Rodriguez-Mateos, Ana (The American journal of clinical nutrition, 2019)
Aronia melanocarpa is a rich source of (poly)phenols. Previous research has demonstrated that these berries may provide cardiovascular health benefits in high-risk populations. However, very few studies have investigated the effects of daily consumption of dietary achievable amounts of the berries in healthy subjects. The aim of this study was to investigate the effects of aronia berries on vascular function and gut microbiota composition in a healthy population. A double-blind, placebo-controlled, parallel designed study was conducted in 66 healthy men randomly allocated to consume a (poly)phenol-rich extract (116 mg, 75 g berries), a whole fruit powder (12 mg, 10 g berries), or placebo (maltodextrin) for 12 wk. Flow-mediated dilation (FMD), arterial stiffness, blood pressure, heart rate, and serum biochemistry were assessed. Plasma (poly)phenol metabolites were analyzed by LC-MS. Gut microbiota composition was determined via 16S rRNA sequencing in stool samples. Consumption of aronia whole fruit and extract powder for 12 wk led to a significant increase in FMD over control of 0.9% ± 0.4% (95% CI: 0.13%, 1.72%) and 1.2% ± 0.4% (95% CI: 0.36%, 1.97%), respectively. Acute improvements in FMD were also observed 2 h after consumption of aronia extract on day 1 (1.1% ± 0.3%, P = 0.003) and 12 wk later (1.5% ± 0.4%, P = 0.0001). Circulating plasma phenolic metabolites increased upon consumption of the aronia treatments. Although no changes were found in gut microbiota diversity, consumption of aronia extract increased the growth of Anaerostipes (+10.6%, P = 0.01), whereas aronia whole fruit showed significant increases in Bacteroides (+193%, P = 0.01). Correlation analysis identified significant associations between changes in FMD, aronia-derived phenolic metabolites, and specific gut microbial genera. In healthy men, consumption of aronia berry (poly)phenols improved endothelial function and modulated gut microbiota composition, indicating that regular aronia consumption has the potential to maintain cardiovascular health in individuals at low risk of cardiovascular disease. This trial was registered at CLINICALTRIALs.gov as NCT03041961.